2019
DOI: 10.1002/ana.25573
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Galactosylceramide as Potential Treatment for CLN3 Disease

Abstract: Objective: CLN3 disease is the commonest of the neuronal ceroid lipofuscinoses, a group of pediatric neurodegenerative disorders. Functions of the CLN3 protein include antiapoptotic properties and facilitating anterograde transport of galactosylceramide from Golgi to lipid rafts. This study confirms the beneficial effects of long-term exogenous galactosylceramide supplementation on longevity, neurobehavioral parameters, neuronal cell counts, astrogliosis, and diminution in brain and serum ceramide levels in Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The hyperactive phenotype prominent in vehicle-treated Cln3 Δex7/8 mice is described for the first time here in mice at of 18 weeks of age. This was not previously documented in Cln3 Δex7/8 mice at 40 weeks of age [ 28 ]. This suggests that, at a young age, Cln3 Δex7/8 mice express a distinct behavioral phenotype prior to onset of more severe CLN3 disease symptoms, including motor decline.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The hyperactive phenotype prominent in vehicle-treated Cln3 Δex7/8 mice is described for the first time here in mice at of 18 weeks of age. This was not previously documented in Cln3 Δex7/8 mice at 40 weeks of age [ 28 ]. This suggests that, at a young age, Cln3 Δex7/8 mice express a distinct behavioral phenotype prior to onset of more severe CLN3 disease symptoms, including motor decline.…”
Section: Discussionmentioning
confidence: 48%
“…This variation among sexes is not a new observation in this disease. We documented this in another study using exogenous galactosylceramide as potential treatment for CLN3 disease [ 28 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The therapeutic approach in this study consisted of treating Cln3 Δex7/8 mice with daily injections of GalCer over 40 weeks. GalCer supplementation resulted in promising outcomes improving some neurobehavioral aspects of the disease, increasing longevity of male and female mice, in addition to reducing ceramide levels in homozygous Cln3 Δex7/8 mouse brain from males and females [23].…”
Section: Discussionmentioning
confidence: 99%
“…A short-term study of injecting GalCer in homozygous Cln3 Δex7/8 mice for a period of 17 weeks resulted in significant improvements in the course of CLN3 disease including reduced ceramide levels, subunit C accumulation and gliosis in specific brain regions. This led to a prolonged trial of 40 weeks with exogenous GalCer that demonstrated beneficial effects on neurobehavioral and biochemical parameters, and increase in longevity of homozygous Cln3 Δex7/8 mice [23].…”
Section: Introductionmentioning
confidence: 99%